2011
DOI: 10.1007/jhep02(2011)059
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Regge trajectories of non-strange mesons

Abstract: We analyze the asymptotic behavior of Regge trajectories of non-strange mesons. In contrast to an existing belief, it is demonstrated that for the asymptotically linear Regge trajectories the width of heavy hadrons cannot linearly depend on their mass. Using the data on masses and widths of ρ J −− , ω J −− , a J ++ and f J ++ mesons for the spin values J ≤ 6, we extract the parameters of the asymptotically linear Regge trajectory predicted by the finite width model of quark gluon bags. As it is shown the obtai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The FWM [16,17] is able to successfully describe a variety of the lattice QCD thermodynamics data [71][72][73] at vanishing baryonic chemical potential. Also its predictions for the Regge trajectories of non-strange and strange mesons [27] were successfully confirmed by the thorough analysis of both the real and the imaginary parts of the leading Regge trajectories [37] of ρ J −− , ω J −− , a J ++ and f J ++ mesons for the spin values J ≤ 6 and the ones of K * J P mesons of isospin 1 2 , parity P = (−1) J and spin values J ≤ 5. One of the most important predictions of the FWM [16,17] is that at vanishing baryonic chemical potential the QG bags are strongly suppressed (by a factor of fifteen-sixteen order of magnitude) In other words, according to the FWM [16,17] at √ s N N = 4.9 GeV the QG bags can be formed.…”
Section: Figmentioning
confidence: 65%
See 2 more Smart Citations
“…The FWM [16,17] is able to successfully describe a variety of the lattice QCD thermodynamics data [71][72][73] at vanishing baryonic chemical potential. Also its predictions for the Regge trajectories of non-strange and strange mesons [27] were successfully confirmed by the thorough analysis of both the real and the imaginary parts of the leading Regge trajectories [37] of ρ J −− , ω J −− , a J ++ and f J ++ mesons for the spin values J ≤ 6 and the ones of K * J P mesons of isospin 1 2 , parity P = (−1) J and spin values J ≤ 5. One of the most important predictions of the FWM [16,17] is that at vanishing baryonic chemical potential the QG bags are strongly suppressed (by a factor of fifteen-sixteen order of magnitude) In other words, according to the FWM [16,17] at √ s N N = 4.9 GeV the QG bags can be formed.…”
Section: Figmentioning
confidence: 65%
“…Before analyzing the hadronic mass spectrum in a thermal environment it is necessary to remind that the question of whether the experimental mass spectrum of hadrons given in the Particle Data Group tables coincides with the spectrum suggested by R. Hagedorn is of great interest nowadays [29][30][31]. However, almost all discussions of the hadron mass spectrum simply ignore the width of resonances, whereas long ago it was found that the large resonance width may essentially modify the spectrum [16][17][18][32][33][34][35][36][37]. Therefore, it is important to study the effective mass spectrum of hadrons having a physical width.…”
Section: Hadron Resonance Gas Model With Gaussian Mass Attenuationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in [8] the estimates based on the Hagedorn mass spectrum inclusion were done without accounting for the large resonance width and without knowing the branching ratios of these hypothetical resonances. Although the mass dependence of width of heavy resonances was found within the finite width model of quark gluon bags [46,47] and recently it was successfully verified on the Regge trajectories of heavy mesons [48], the possible channels of their decays and the corresponding branching ratios are completely unknown yet. However, the more serious issue is that the finite width model [46,47] explains that the huge deficit of the empirical hadronic spectrum compared to the Hagedorn one is due to the fact that the 'missing' hadrons with the masses above 2.5 GeV and with the large width are the quark gluon bags, which are extremely suppressed (by fifteen-sixteen orders of magnitude) compared to the stable hadrons up to the temperatures of about half of the Hagedorn temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, however, the importance of finite width of heavy/large quark gluon plasma bags was realized [21][22][23]. Both the theoretical estimates [22,23] and the analysis of the asymptotic Regge trajectories of non-strange mesons [37] indicate that the width of the quark gluon bag of the volume V with the mass M being heavier than M 0 ≈ 2.5 GeV is Γ = γ(T ) V V0 (here V ≥ V 0 = 1 fm 3 ). Since even at T = 0 the value γ(T = 0) ≈ 400 MeV is large, we conclude that the short life time t lif e (V ) = 1/Γ(V ) of such bags can, in principle, modify our conclusions about the metastable states λ n>0 .…”
Section: Finite Volume Analogs Of Phasesmentioning
confidence: 99%